Overview Analisis Sistem Manajemen Keselamatan pada Industri Pertambangan Di Beberapa Negara - Wardani, Hertanti Kusuma; Khamim, Nur (Syntax Idea, 2021)
The effort to reduce and eliminate the dangers of mining activities by preventing losses that is by implementing the application of safety management. Safety management systems are applied throughout the world. The world gets permission for industrial safety and health to get occupational safety and health. This safety management system is not only applied in Indonesia but also applied in several other countries such as South Korea, Singapore, Malaysia and Australia. In this study an analysis of the differences in the safety management system in these countries with an outline with the aim to carry out an analysis of the safety management system in large rock countries. The comparison obtained from the management system required and applied by the government regarding the safety system in these countries. For Indonesia and Singapore, a safety management system must be implemented in industrial companies, whereas for countries such as South Korea the safety management system is voluntary in other words the safety management system is implemented voluntarily by the industry. Australia is more applying safety management system standards and references for industrial needs. Safety management systems in Australia, South Korea and Malaysia are being readjusted to suit industry needs.